2012
DOI: 10.1016/j.jvs.2011.10.127
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary findings in quantification of changes in septal motion during follow-up of type B aortic dissections

Abstract: Reduction of IS motion in AD is seen with short-term and midterm follow-up. Intersubject variability of this trend is high at short-term follow-up but low at midterm follow-up. Detailed analysis of IS motion parameters indicate reduction of IS contraction and IS compliance with time. This has potential implications for endovascular management of type B aortic dissections, as expansion of aortic stent grafts can be limited by a stiff IS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 22 publications
3
31
0
Order By: Relevance
“…As discussed in the paper by Alimohammadi et al [12], the displacements obtained for this case study are comparable to those reported by clinical imaging studies [17,27]. However, in some acute settings, abnormal motion of the IF leading to the obstruction of distal aortic branches can be observed [34].…”
Section: Limitationssupporting
confidence: 87%
See 1 more Smart Citation
“…As discussed in the paper by Alimohammadi et al [12], the displacements obtained for this case study are comparable to those reported by clinical imaging studies [17,27]. However, in some acute settings, abnormal motion of the IF leading to the obstruction of distal aortic branches can be observed [34].…”
Section: Limitationssupporting
confidence: 87%
“…where [17]. The tuning of Ki and Kj is based on patient-specific displacement data obtainable, for instance, from cine 2D MR images.…”
Section: Description Of the Methodsmentioning
confidence: 99%
“…The change in cross-sectional area of the TL and FL was calculated from ECG-gated CT scans by Ganten et al [ 33 ] and they observed a mean TL cross-sectional area reduction (-4.4%), comparable to the A * values shown in Figure 3 a. The median IF oscillation observed by Ganten et al [ 33 ] was 1.3 mm , while Karmonik et al [ 34 ] reported average IF displacements of approximately 0.48-0.68 mm from MRI data. These values compare favourably with the IF deformation shown in Figure 2 .…”
Section: Discussionmentioning
confidence: 83%
“…If it transpires that the imaging data of Yang et al [ 35 ] is more characteristic of true flap motion than previous reports [ 33 , 34 ], then it is clear that the loss of accuracy through the rigid wall simplification would be exacerbated. However, further developments are required, particularly in calculating the vessel wall properties of a dissected aorta, before this technology will be able to truly predict the fluid and solid dynamics of this condition.…”
Section: Discussionmentioning
confidence: 96%
“…27 FL patency status was detected from the arterial and venous phase of postoperative CTA, and it is conceivable that this is not the most sensitive or specific method for analyzing this end point given reports on efficacy of various dynamic MRI techniques. 32,33 …”
Section: Discussionmentioning
confidence: 99%